OBSERVASI, WAWANCARA DAN ANGKET TERKAIT LITERASI DIGITAL DI SDN 89 PALEMBANG - Cica Ranika; Riska Rahmadilla; Novita dwi lestari; Agnes Lorensia; Azizil Alim (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the level of digital literacy of students at SDN 89 Palembang  through observation, interviews, and questionnaires. Digital literacy is an individual's ability  to understand, use, and evaluate information through digital media effectively and responsibly.  This study used a descriptive qualitative approach with subjects of grades (II and IV),  homeroom teachers, and the principal. Data were collected through observations of digital based learning activities, in-depth interviews with teachers and students, and questionnaires to  measure the level of understanding and use of digital technology in the school environment. The results showed that most students already have basic skills in operating digital devices  such as laptops and gadgets, but are still limited in aspects of digital ethics, data security, and  the ability to evaluate information from the internet. Teachers play an important role in guiding  students to use technology positively through learning activities integrated with digital literacy.  This study recommends improving teacher training and providing adequate digital resources to  support 21st-century learning in elementary schools. The results of the questionnaire showed  that the level of digital literacy of students is at 70% of students who do not like reading long  texts on cellphones or infocus because they get bored quickly. 50% of students rarely seek  learning information using or tablets. Nearly 100% of students are now proficient in using  learning apps like Google and YouTube. Most students understand lessons more easily when  teachers use technology like infocus or instructional videos. They hope that technology enabled learning can be more frequent and varied.